Evolution of India’s transformation: From post-independence nation-building to digital society, inclusion, and development challenges - Gayatri Sunkad (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2026)
The concept of “transformation” refers to significant changes that are observable and impactful in various aspects of society. In India, transformation began post-independence but can be traced back to the freedom movements, which also marked the early stages of change. This study explores the evolution of transformation in India, focusing on its diverse impacts, particularly in the fields of science, technology, economics, and culture. The primary aim of the research is to examine the key drivers behind India’s transformation, from the historical context of independence to the current era of digital revolution. The study employs a qualitative research method, analysing historical data, government reports, and technological advancements that have shaped the country. A thematic analysis reveals that while India experienced gradual shifts in its economy, culture, and technological landscape, the most significant changes occurred with the advent of digitalization, which has revolutionized communication, governance, and business. The conclusion highlights that transformation in India continues to unfold, influenced by both traditional factors and new-age technological innovations.